Moral Messages in the Film Cinta Subuh by Ali Farighi: A Semiotic Analysis of Roland Barthes - Mila Salsaby; Rubino (Community Medicine and Education Journal, 2023)
Film is one of the mass communication media that is currently favored by teenagers. This media is considered capable of being an alternative to preaching to the general public. One of them is Cinta Subuh’s film. This film is a medium for da’wah because, in this film, we can learn many moral messages. This study aimed to discuss moral values and understand the meaning of the moral message shown in the film "Cinta Subuh by Ali Farighi". This research is a descriptive qualitative research using a semiotic analysis model by Roland Barthes which is carried out in three stages, namely denotation, connotation, and myth. The data collection technique was carried out by directly analyzing the contents of the film Cinta Subuh to find out the description of the characteristics of the content and draw inferences from the content featured in the film. The results of the research contain moral values that are categorized as: 1) Morals to Allah such as devotion to Allah, love for Allah, sincerity, khauf and king', gratitude, muraqobah, repentance, benevolence, and trust. 2) Morals towards oneself, such as patience, faithfulness, humility, gratitude, istiqamah, iffah, forgiveness, and trust. 3) Morals towards fellow human beings, such as maintaining good relationships, telling the truth, not belittling others, being kind, and loving. 4) Morals towards the environment, such as the prohibition of causing damage to the earth, the prohibition of damaging plants and animals, the prohibition of polluting seawater, maintaining environmental safety, maintaining physical hygiene, and others.